Introduction to the Special Issue: Microbiological Safety and Quality of Foods - Alyexandra Arienzo; Valentina Gallo; Chiara Fanali; Giovanni Antonini (Foods, 2022)
Recent shifts in food production, processing and distribution, linked to the globalization of the food trade and the need to meet new consumers habits, are continuously challenging global food systems [...]